2008
DOI: 10.1152/ajprenal.00493.2007
|View full text |Cite
|
Sign up to set email alerts
|

Membrane current oscillations in descending vasa recta pericytes

Abstract: We investigated the origin of spontaneous transient inward current (STIC) oscillations in descending vasa recta (DVR) pericytes. In cells clamped at Ϫ80 mV, angiotensin II (ANG II; 10 nmol/l) induced oscillations with mean amplitude and frequency of Ϫ65.5 pA and 1. METHODS Isolation of DVR.Investigations involving animal use were performed according to protocols approved by the Institutional Animal Care and Use Committee of the University of Maryland. Kidneys were harvested from Sprague-Dawley rats (100 -150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 53 publications
4
36
0
Order By: Relevance
“…C: overall current, calculated as the sum of the currents crossing the cytosol and the microdomains, and the leak current (taken as Ϫ8 pA, assuming a 10-G⍀ seal). agonist (ANG II) stimulation (36,52,56) and KCl depolarization (36, 56) when IP 3 R and RyR stores are separated. Other authors have investigated the minimal model requirements for generation of oscillations and concluded that RyR participation is not a requisite feature (4, 16).…”
Section: Discussionmentioning
confidence: 99%
“…C: overall current, calculated as the sum of the currents crossing the cytosol and the microdomains, and the leak current (taken as Ϫ8 pA, assuming a 10-G⍀ seal). agonist (ANG II) stimulation (36,52,56) and KCl depolarization (36, 56) when IP 3 R and RyR stores are separated. Other authors have investigated the minimal model requirements for generation of oscillations and concluded that RyR participation is not a requisite feature (4, 16).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we suspected endothelial expression of a ouabain-sensitive isoform in rat vasa recta because ouabain, in nanomolar concentrations, has clear effects on DVR endothelial Ca 2ϩ content and concentration (35). In addition, basal [Ca 2ϩ ] CYT and the frequency of spontaneous transient inward currents attributable to the action of Ca 2ϩ on Ca 2ϩ -dependent chloride channels are increased by ouabain in DVR pericytes (49). Given the important roles of the ␣2 isoform in the extrarenal vasculature, we explored its expression using a subtype-specific antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue, whether enzymatically digested or undigested, was then transferred to microperfusion buffer (in mM): 140 NaCl, 10 NaAcetate, 5 KCl, 1.2 MgCl 2, 2 Na2HPO4/ NaH 2PO4, 1 CaCl2, 5 alanine, 5 glucose, 5 HEPES, and 0.5 g/dl albumin, pH 7.4, and stored at 4°C. At intervals, DVR were isolated and either transferred to microscope slides for fixation and immunostaining (23,24) or to the stage of an inverted microscope for microperfusion and fluorescence measurements (32,35,49).…”
Section: Isolation Of Dvrmentioning
confidence: 99%
See 2 more Smart Citations